Avaliação do efeito de receptores purinérgicos em neutrófilos cultivados in vitro com formas promastigotas de Leishmania amazonensis ou Leishmania braziliensis - Otoni Alves de Oliveira Melo Júnior (2015)
The presence of ATP in the extracellular environment, may be interpreted as a "danger signal" by neutrophils, and their effects are dependent on factors such as the action of enzymes ectonucleosídeo 5'-triphosphate diphosphohydrolase - E-NTPDase (CD39) and 5 'nucleotidase (CD73), in addition of ATP purinergic receptors. The present study evaluated the involvement of purinergic receptors in neutrophils immune response stimulated in vitro, with Leishmania amazonensis or Leishmania braziliensis. Initial viability analysis of neutrophils infected with L. amazonensis or L. braziliensis showed that the percentage of viable cells was not changed. Higher percentage of L. braziliensis interaction with neutrophils was observed when compared to L. amazonensis. Although the analysis of the frequency of neutrophils expressing CD39 and CD73 was similar, regardless of the stimulus, only L. amazonensis- stimulated culture showed increased CD73 expression. Thus, there would be an increase in adenosine, which could contribute to a less pro-inflammatory microenvironment during infection by L. amazonensis in neutrophils, when comparing with infection L. braziliensis. These findings were reinforced by higher intracytoplasmic levels of ROS and NO in neutrophils in the presence of L. braziliensis, when compared to L. amazonensis. To evaluate the possible involvement of the purinergic receptors in the immune response, four compounds were used: MRS 1754 (antagonist of A2B receptor), αβ-methylene (CD73 blocking activity), suramin (antagonist of P2X and P2Y) and NECA (agonist of A1 and A2 receptors). This approach showed that neutrophils stimulated with L. amazonensis in the presence of MRS 1754 and NECA induce increased NO synthesis, suramin induces increased synthesis of ROS and NO, while the αβ methylene reduced levels of ROS. Neutrophils stimulated with L. braziliensis and treated with MRS 1754 and suramin exhibited increased ROS synthesis, treatment with NECA induced increase in NO production, while the αβ-methylene reduced ROS levels. After the realization of this study, it was evident that L. braziliensis is capable to induce neutrophil in a more pro-inflammatory profile, inducing high levels of ROS and NO, while the L. amazonensis showed higher CD73 enzyme activity, resulting in an interaction with neutrophils more favorable to the parasite.